Investigating the role that the Southern Ocean biological pump plays in determining global ocean oxygen concentrations and deoxygenation - Keller, David; Oschlies, Andreas (2014)
Global ocean circulation connects marine biogeochemical cycles through the long-range transport of nutrients and oxygen with the Southern Ocean (SO) acting as a water mass crossroads. The biological pump in the SO has been shown to play an important role in these dynamics and the amount of export production is known to have a large impact on remote deep ocean nutrients and dissolved inorganic carbon. However, the role that the SO biological pump plays in determining ocean oxygen concentrations is less well understood. In this study we investigate these dynamics by shutting off the SO biological pump in two different general ocean circulation models, each of which is coupled to a different prognostic biogeochemical model. Our results indicate that the present day SO biological pump is responsible for reducing oxygen levels in the deep ocean by up 70 mmol m-3. The SO biological pump also removes nutrients that would otherwise be used to fuel productivity and subsequently reduce oxygen in mid- to low-latitude sub-surface waters (i.e., without the SO biological pump, oxygen is lower in these regions due to higher productivity). Since SO productivity and export is expected to change in response to climate change we also examine the role that these changes may play in future ocean deoxygenation.